Ответы и объяснения

Лучший Ответ!
2013-06-18T15:14:19+00:00

√(4x - 3) = x

(√(4x - 3))² = x²

4x - 3 = x²

-x² + 4x - 3 = 0 | × (-1)

x² -4x + 3 = 0

 

D = b² - 4ac = (-4)² - 4 × 1 × 3 = 16 - 12 = 4

 

x₁,₂ = (-b ± √D) ÷ 2a

 

x₁ = (4 + 2) ÷ 2 = 3

x₂ = (4 - 2) ÷ 2 = 1

 

3 + 1 = 4

 

Ответ: 4.

2013-06-18T15:33:21+00:00

√(4x - 3) = x

(√(4x - 3))² = x²

4x - 3 = x²

-x² + 4x - 3 = 0 | × (-1)

x² -4x + 3 = 0 

D = b² - 4ac = (-4)² - 4 × 1 × 3 = 16 - 12 = 4

x₁,₂ = (-b ± √D) ÷ 2a

x₁ = (4 + 2) ÷ 2 = 3

x₂ = (4 - 2) ÷ 2 = 1

3 + 1 = 4.

так наверное!!!